Structural adjustment and employment issues in Barbados: country paper (ILO. PREALC Caribbean Office Port of SpainTT, 1991)
Identifies policies for economic expansion during 1988 viz. private sector concessions; revitalization of the agricultural sector; improved competitiveness in the manufacturing sector; tourism; construction; consensus policy; incomes policy; credit controls and interest rates on savings. Considers effect of adjustment policies on employment and unemployment focussing on measures to temper the effect of adjustment.
DC